Exploring Biophilic Design in Eco-Tourism: A Comparative Assessment of Environmental and Architectural Synergy in Tropical and Subtropical Contexts - Fagam, Saleem Abubakar; Sagada, Musa Lawal; Yakubu, Kashim Ibn; Aule, Thomas Terna; Tijjani, Zakari Abdullahi (Faculty of Natural and Applied Sciences Journal of Applied and Physical Sciences, 2025)
This study explores the integration of biophilic design principles in resort architecture across three diverse ecological settings: Yankari Game Reserve in Bauchi, Nigeria; Jean Michel Cousteau Resort in Vanua Levu Island, Fiji; and Kailumcito at the Camptel Resort, Mexico. Biophilic design—an approach that fosters human connection to nature through architectural features—has been recognised for its potential to enhance well-being, environmental sustainability, and user satisfaction. Using qualitative analysis of five key biophilic design features (natural lighting and ventilation, local materials, views and prospects, natural features, and natural forms and processes), the study reveals that only natural lighting and ventilation scored positively across all cases. The other elements were either poorly implemented or overlooked, particularly local material use and natural forms, indicating a disconnect between architectural intent and environmental context. These findings are linked to prior research emphasising the psychological and ecological benefits of immersive natural environments, yet highlight a persistent implementation gap in the limited use of local materials. The study recommends greater policy support, design education, and community engagement to promote biophilic design. It also suggests further research into long-term user experiences in biophilic spaces. This research contributes to sustainable architectural practice by identifying opportunities to align built environments more closely with natural ecosystems.